Modeling Catchment-Scale Nitrogen Losses Across a Land-Use Gradient in the Subtropics - Hajati, Mithra-Christin; White, Shane; Moosdorf, Nils; Santos, Isaac R. (Frontiers in Earth Science, 2020)
Changing land use in subtropical and tropical catchments to farmland can result in higher nitrogen (N) loss to aquatic ecosystems. Here, we developed a lumped water and N balance model to estimate regional N losses to creeks at catchment scale within understudied subtropical catchments in Australia. The conceptual water balance model CoCa-RFSGD was extended by the nitrogen mass balance in top and sub soil by adding nitrogen cycle transformation estimates depending on meteorological, soil and land use properties. The model estimates the impact of pristine and agricultural land use on catchment-wide water quality using only loworder creek samples as water quality measurements of nitrate and nitrite (NOx), with increased model performance with increased agricultural coverage. The model revealed that an agricultural proportion of 3% in the study site drove a 3.5-fold increase of N losses to creeks and a 6.7-fold increase of N losses to the atmosphere compared to catchments without agriculture. Agricultural land use lost 92 kg-N ha−1, of which 85% evaded to the atmosphere and 15% discharged via surface waters. A change from forest to cleared land may increase the total denitrification potential of a catchment. Overall, our lumped model provides a simple but effective tool to upscale local aquatic water quality measurements to the catchment scale, allowing assessment of changing land use on aquatic N loads in areas with limited data availability.